2003
DOI: 10.2337/diacare.26.9.2518
|View full text |Cite
|
Sign up to set email alerts
|

Within-Trial Cost-Effectiveness of Lifestyle Intervention or Metformin for the Primary Prevention of Type 2 Diabetes

Abstract: OBJECTIVE-The Diabetes PreventionProgram (DPP) demonstrated that intensive lifestyle and metformin interventions reduced the incidence of type 2 diabetes compared with a placebo intervention. The aim of this study was to assess the cost-effectiveness of the lifestyle and metformin interventions relative to the placebo intervention.RESEARCH DESIGN AND METHODS-Analyses were performed from a health system perspective that considered direct medical costs only and a societal perspective that considered direct medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(94 citation statements)
references
References 22 publications
2
92
0
Order By: Relevance
“…Of these, 6 cost-only studies (2023, 26, 27) and 6 cost-effectiveness studies (19, 24, 25, 2830) provided information on the actual cost of diet and physical activity promotion programs, and 22 contributed cost-effectiveness estimates of the programs (19, 24, 25, 2846). Fourteen studies were U.S.-based (19–24, 26, 27, 31, 3538, 46). No cost–benefit studies were identified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 6 cost-only studies (2023, 26, 27) and 6 cost-effectiveness studies (19, 24, 25, 2830) provided information on the actual cost of diet and physical activity promotion programs, and 22 contributed cost-effectiveness estimates of the programs (19, 24, 25, 2846). Fourteen studies were U.S.-based (19–24, 26, 27, 31, 3538, 46). No cost–benefit studies were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 studies that reported the actual costs of implementing the program (2031), only 4 included costs for identifying persons at increased risk (22, 24, 27, 29). The major cost driver was staff time to deliver the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intervention start-up costs, fixed costs of sustaining the intervention, and marginal costs of adding additional participants to the intervention will be differentiated because they are relevant for different decisions: whether to implement the intervention in the first place and whether to sustain or expand it over time. We will use simulation models, similar to those in Diabetes Prevention Program and Sequenced Treatment Alternatives to Relieve Depression, 68,73,74 to analyze incremental cost-effectiveness ratios during the trial and projected into 5-, 10-, 20-, 30-year, and lifetime horizons. Cost-utility estimates with different time horizons will be useful for stakeholders deciding on program implementation.…”
Section: Methodsmentioning
confidence: 99%